The role of eco-economy in recovering from crisis - Sarbovan Marina, Luminita (Economics of Agriculture, 2010)
During the current crisis, the ecological aspects of the economy become more important, being one of the major issues because they are promising a healthy way of economic recovery. In order to become more effcient, in this branch, most of the reproaches coming from the farmers and are focused on the low subvention, or slow and too long terms financing flows involved in farming industry. In Romania, the state subventions also go for eco-ruralproduction, and fnancing this sector helps the recovery from the crisis, fact confrmed by the raising trend evolution of the bio-production and retail in our country. The trend is for the "green" factors of recovery to be diversifed and implemented in all branches of activity.